Russian migrants to Russia: Assimilation and local labor market effects - Olga Lazareva (IZA Journal of Migration, 2015)
As a result of the collapse of the Soviet Union, five million Russian and Russian-speaking people repatriated to Russia during 1990 - 2002. I use this natural experiment to study labor market assimilation of migrants and their effect on the employment and wages of the local population. I show that male immigrants were fully integrated into the labor market, while female immigrants faced significant wage and employment gaps upon arrival, and their assimilation was slow. Using an IV strategy to account for the endogenous choice of location, I find a negative effect of the inflows of immigrants on the local population's employment but not on wages. The initial displacement effects are particularly large for men, but they disappear after about ten years after the peak of migration wave.
Keywords: J61; J31; J64; 330; Migration; Assimilation; Wages; Employment; Russia